PENERAPAN PEMBELAJARAN AKTIF DENGAN TEKNIK ROTASI REFLEKSI TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN GURUN PANJANG KABUPATEN PESISIR SELATAN - Mardiyan, Harlan - (Pendidikan Matematika, 2014)
This research is motivated by the students understanding of mathematicalconcepts are still low and the student receives only a summary of the results of theteacher without trying to find themselves the results summarized. This is evidentfrom the results of learning mathematics class VII student enrolled in the classVIII MTsN Gurun Panjang of the school year 2014/2015. The study aims todetermine whether the active learning techniques Reflection Rotation effect on theunderstanding of mathematical concepts eighth grade students MTsN GurunPanjang. The study was pre-experimental research, the research design of pretestand post-test. The subjects were all eighth grade students MTsN GurunPanjang 2014/2015 academic year consisting of one class. Research instrument isa test of understanding of mathematical concepts. The form of the test used is innarrative form with divaliditas by the teacher. Hypothesis test used was a twowayt-test, the value t = 24.98 and t(Î±/2) = 2.07 Hypothesis accepted because t >t(Î±/2) so that the hypothesis is accepted at the significance level Î± = 0.05. It canbe concluded that there are significant active learning with the EngineeringRotation Reflection on understanding mathematical concepts grade students VIIIMTsN Gurun Panjang .